IDENTIFICATION OF POTENTIAL LANDSLIDE AREAS IN NUSANIWE SUB-DISTRICT USING SLOPE MORPHOLOGY METHOD - Latue, Philia Christi; Rakuasa, Heinrich (Journal of Data Analytics, Information, and Computer Science, 2024)
This study aims to identify landslide-prone areas in Nusaniwe District using the Slope Morphology Method (SMORPH), which is based on slope and slope shape analysis. The research method uses the Slope Morphology Method (SMORPH) to assess landslide potential in Nusaniwe District. The analysis was carried out by mapping the slope gradient and slope shape in the area to determine areas at high risk of landslides. Topographic and geological data were collected and analyzed to identify factors that contribute to landslide risk. The results of the analysis show that  complex geological and topographic conditions in Nusaniwe District increase the risk of landslides. Areas with high slope gradients and steep slope shapes are identified as the most landslide-prone areas. This assessment revealed a significant relationship between slope gradient, slope shape, and landslide potential in the area. The conclusion is that the analysis of slope and slope shape using the Slope Morphology Method (SMORPH) is effective in identifying landslide-prone areas in Nusaniwe District. To reduce landslide risk, interdisciplinary collaboration, community education, and development of effective mitigation strategies are needed. These findings provide a basis for planning and implementing landslide prevention measures in areas with similar conditions. Keywords: Landslide, Nusaniwe, Slope Morphology